(3GdCQHYhf MOjKkGs - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s ((3QVi GdOjf eMeO Hf eQJVi GdYHGSjs)
(3ChdgG (B:s
(3hHYO aEf GdabjQ Edi Gddg GdZfj HgGAGdOjf eMeO GdYGedjjbhd CYXe GdeWGdH hGdeaGNQ HYO GdEjeGf HGddg hGdjhe GdBNQ EdG Hfbd GdMOjK hQhGjJg hVHWg s
(3BNQgG (B:s
(3HUOb gDdGA ajeG jdbhfg Edjc ef NaGjG GdgHGJ GdadcjIhggfG bWY GdcdGe TGcQkG Gddg Ydi Jhajbg heUdjkG Ydi CTQa GdCfGe hGdO GdgGOjf Edi OGQ GdSdGe s
(3GdfSNI HgG MhGTs
(3HChdgG JedcGJs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs